2012
DOI: 10.1029/2011jc007679
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of the Western Mediterranean Deep Water after winter 2005: Time scales and deep cyclone transport

Abstract: [1] This work is dedicated to the study of the propagation of the Western Mediterranean Deep Water (WMDW) formed in the Gulf of Lions during the exceptional winter 2005. A simulation of the 1998-2008 period has been carried out with an eddy-resolving Ocean General Circulation Model of the Mediterranean Sea, driven by interannual high-resolution air-sea fluxes. This study first presents a validation of the recently improved model configuration against satellite observations. Then, we assess the ability of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(212 citation statements)
references
References 75 publications
5
207
0
Order By: Relevance
“…For the period 1989-2001, data come from the SSH monthly seasonal cycle of the previous simulation with a time shift of 5 months in the seasonal cycle to follow the cycle of GLORYS-1 in the near Atlantic domain, there is thus no interannual variability before 2002. An exhaustive description of this methodology can be found in Beuvier et al (2012). GLORYS-1 anomalies in the Atlantic buffer zone (11 • W-7.5 • W) have an amplitude of about 14 cm, in agreement with AVISO products, which were assimilated in the GLORYS-1 reanalysis.…”
Section: Morce-med-variable Atlantic From Reanalysis Assimilating Altmentioning
confidence: 61%
“…For the period 1989-2001, data come from the SSH monthly seasonal cycle of the previous simulation with a time shift of 5 months in the seasonal cycle to follow the cycle of GLORYS-1 in the near Atlantic domain, there is thus no interannual variability before 2002. An exhaustive description of this methodology can be found in Beuvier et al (2012). GLORYS-1 anomalies in the Atlantic buffer zone (11 • W-7.5 • W) have an amplitude of about 14 cm, in agreement with AVISO products, which were assimilated in the GLORYS-1 reanalysis.…”
Section: Morce-med-variable Atlantic From Reanalysis Assimilating Altmentioning
confidence: 61%
“…In the NW Mediterranean, numerical studies have pointed out the role of cyclonic eddies in the export of newly formed deep waters [Herrmann et al, 2008;Beuvier et al, 2012]. Herrmann et al [2008] found that about one-third of the newly formed deep waters is exported southward by such cyclonic structures.…”
Section: 1002/2016jc012144mentioning
confidence: 99%
“…Herrmann et al [2008] found that about one-third of the newly formed deep waters is exported southward by such cyclonic structures. In those simulations, the cyclones are large mesoscale surface-intensified cyclones lacking realistic characteristics, certainly because of a too coarse model resolution: 3 km in Herrmann et al [2008] and 6-8 km in Beuvier et al [2012]. To correctly resolve 5 km radius SCVs, a horizontal resolution of 1 km as in Damien [2015] seems to be needed.…”
Section: 1002/2016jc012144mentioning
confidence: 99%
“…The model used in this work is a free surface ocean general circulation model NEMO (Madec and NEMO-Team., 2008) in a regional configuration called NEMO-MED12 (Beuvier et al, 2012a). NEMO-MED12 covers the whole Mediterranean Sea and also extends into the Atlantic Ocean to 11 • W (buffer zone).…”
Section: Description Of the Modelmentioning
confidence: 99%
“…Simulated 3 H-3 He concentrations in the water column are compared with observations from R/V Meteor cruises: M5/6-1987M5/6- , M31/1-1995M5/6- , M44/4-1999M5/6- , M51/2-2001M5/6- , M84/3-2011M5/6- , and Poseidon 232-1997. These data allow us to critically examine the dynamics of the NEMO-MED12 ocean model (Nucleus for European Modelling of the Ocean, in a regional configuration for the Mediterranean Sea called MED12) (Lebeaupin Brossier et al, 2011;Beuvier et al, 2012a;Palmiéri et al, 2015) and to evaluate the ability of this model to reproduce the main features of the circulation and mixing of the Mediterranean Sea water masses and their interannual variability, including the exceptional events observed in the ventilation of the deep waters.…”
Section: Introductionmentioning
confidence: 99%